The Role Of Village-Owned Enterprises (Bumdes) In Empowering Women's Economy In Simpang Dolok Village, Batu Bara Regency - Sitorus, Yusriadi; Fadlan, Ahmad; Faried, Annisa Ilmi (Universitas Dehasen Bengkulu, 2026)
Women's economic empowerment in rural areas continues to face complex structural and cultural barriers, including patriarchal norms, domestic double burden, and limited access to economic resources. Village-Owned Enterprises (BUMDes) have been promoted as strategic instruments for rural community economic empowerment; however, the concrete mechanisms of their role in substantively empowering women remain insufficiently studied, particularly in the coastal regions of North Sumatra. This study aims to understand the role of BUMDes in women's economic empowerment in Simpang Dolok Village, Batu Bara Regency, through three key dimensions: access to resources, agency or participation, and control over economic achievements, drawing on Kabeer's (1999; 2005) women's empowerment framework. This study employs a qualitative approach with an intrinsic single-case study design. Data were collected through in-depth interviews, focus group discussions (FGDs), participatory observation, and documentary analysis involving 22 purposively selected informants, comprising BUMDes member and non-member women, BUMDes administrators, village officials, and husbands of key informants. The findings reveal that BUMDes